Compressive behavior of CFRP-steel composite tubed steel-reinforced columns with high-strength concrete. (November 2018) - Wang, Jizhong; Cheng, Lu; Yang, Junlong
Abstract: This paper presents a combined experimental and analytical study on the compressive behavior of FRP-steel composite tubed steel-reinforced columns (FSCSCs) through a total of 14 specimens. The key parameters examined included the cross-sectional shape, the width of grooves on the steel tube, and the number of CFRP sheet layers. The ultimate load-carrying capacity and axial deformation capacity of all circular specimens were strengthened by CFRP layers substantially, whereas the improvement was not observable for square hybrid columns. Meanwhile, the experimental results indicate that the confinement provided by CFRP-steel composite tube is more efficient when no direct axial load was applied on the steel tube, especially in circular specimens. ABAQUS was adopted for establishing an accurate FE model and the excellent agreement had been achieved between the numerical results and experimental results. Parametric studies were performed to investigate the influence of several important parameters using the validated FE model. Based on the results of the parametric analyses and previous studies, a proposed equation shows a great performance in predicting the load carrying capacity of experimental ones with high strength concrete in this study and other literature. Highlights: 14 FSCSCs with high strength concrete (C80) have been analyzed. Circular FSCSCs offer higher load capacity, ductility and dilation properties. Numerical analysis with various design parameters is conducted. A new method for predicting the load capacity of circular FSCSCs is proposed.